Upper limb activity in children with unilateral spastic cerebral palsy: the role of vision in movement strategies. (November 2013) - Savelsbergh, Geert J P; Ledebt, Annick; Smorenburg, Ana R P; Deconinck, Frederik
Abstract : This article reviews the capacity of children with unilateral spastic cerebral palsy (USCP) to (re)organize the available degrees of freedom and to use visual information in interceptive actions during motion with either the impaired or the less‐impaired hand. Atypical reaching movements, such as increased trunk movement or slower wrist velocity, are considered adaptive coordination patterns that are the result of a change in the constraints. It is argued that manipulation of the task context facilitates children with USCP to enhance performance. For example, when reducing the time available to intercept a ball, the children are found to exceed their usual maximum walking speed and to increase range of motion of the elbow. In addition, the children appear to rely on a visual information strategy similar to typically developing children ('bearing angle'), although more variability is observed when using the impaired arm. The implications for interventions are, it should be recognized, that these children adapt to the impairment by reorganizing the movement system and that this process can be influenced by changing the task context. Attention should be paid to the importance of using correct visual cues for initiation and guidance of interceptive actions, which may be provoked by using external visual triggers.